Strategies For Optimizing Catfish Potential Through A Creative Economy Approach In Pasar 60 Village, Batang Arah Tapan Nagari, Basa Ampek Balai Tapan Sub-District, Pesisir Selatan Regency - Okta Pendra; Rika Widiantia; Habibatur Ridhah; Yenty Astarie Dewi (Yayasan Rahmat Islamiyah, 2026)
This study aims to formulate a strategy to optimize catfish potential through a creative economic approach in Pasar 60 Village, Nagari Batang Arah Tapan, Basa Ampek Balai Tapan District, Pesisir Selatan Regency. Although the potential for catfish in this area is quite large, its management is still traditional, minimal innovation, limited access to capital, technology, and digital marketing. This study uses a qualitative descriptive method with data collection techniques in the form of observation, in-depth interviews, and documentation of village catfish farmers. Data analysis was carried out using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach and the IFAS and EFAS matrices to determine the position and direction of the strategy. The results of the study indicate that the right strategy is the SO strategy, namely optimizing strengths and opportunities through the development of processed products such as shredded meat, crackers, and smoked catfish and utilizing social media as a marketing tool. The ST strategy encourages the creation of a distinctive brand for Tapan catfish products; the WO strategy is directed at training in processing and digital marketing; while the WT strategy emphasizes the formation of sharia cooperatives and policy advocacy. The conclusion of this study confirms that the creative economic approach can increase the added value of catfish products, support the strengthening of farmer institutions, and encourage sustainable local economic growth.